Immunogenicity of a bivalent virus-like particle norovirus vaccine in children from 1 to 8 years of age: A phase 2 randomized, double-blind study. Issue 26 (9th June 2022) - Vesikari, Timo; Saez-Llorens, Xavier; Blazevic, Vezna; Lopez, Pio; Lopez, Eduardo; Masuda, Taisei; Mendelman, Paul M.; Liu, Mengya; Sherwood, James; Baehner, Frank; Borkowski, Astrid
Highlights: TAK-214 norovirus vaccine is well tolerated in children from 1 to 8 years of age. Immune responses were similar in two cohorts of 1–3 and 4–8 year-olds. Reactogenicity and immunogenicity were not affected by increasing dosage of TAK-214. Responses were not markedly increased by a second dose in these populations. Despite waning antibodies responses persisted above baseline for at least 6 months. Abstract: Background: Young children can suffer severe consequences of norovirus gastroenteritis. We performed a dose-finding study of a bivalent virus-like particle (VLP) vaccine candidate (TAK-214) in healthy 1–8-year-old children. Methods: In this phase 2 study two age cohorts (1–3 and 4–8 years of age inclusive, N = 120 per cohort) of children enrolled from Finland, Panama and Colombia were initially randomized 1:1:1:1 to four groups which were further split into two equal subgroups, to receive one or two intramuscular doses of four TAK-214 formulations containing 15/15, 15/50, 50/50 or 50/150 μg of GI.1/GII.4c genotype VLPs and 0.5 mg Al(OH)3 at 28 days interval. ELISA Pan-Ig and histoblood group antigen-blocking (HBGA) antibodies against each VLP were measured on days 1, 29, 57 and 210. Parents/guardians recorded solicited local and systemic adverse events (AE) and any unsolicited or serious AEs (SAE). Results: All formulations were well-tolerated across both age cohorts and dosage groups with no vaccine-related SAEs reported. Solicited AEs were mostly mild-to-moderate, resolved quickly, and did not increase after the second dose. Pan-Ig and HBGA responses induced after one dose were only slightly increased by the second dose. Across dose groups at Day 29 after one dose GI.1 Pan Ig seroresponse rates (SRR) were 82–97% and 81–96% and GII.4c SRR were 79–97% and 80–91% in 1–3 and 4–8 year-olds, respectively. Respective rates were to 92–93% and 73–92% for GI.1, and 77–100% and 62–83% for GII.4c at Day 57 following two doses. HBGA responses had similar profiles. Both Pan Ig and HBGA geometric mean titers persisted above baseline up to Day 210. Conclusions: All dosages of TAK-214 displayed acceptable reactogenicity in 1–8-year-old children and induced robust, durable immune responses after one dose which are further increased after two doses.